Hubungan Penatalaksanaan Perawatan Paliatif dengan Kualitas Hidup - Dian Ludfiani; Titik Suhartini (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Terminal illness is a condition where there is no hope for the patient to recover. Palliative measures can help terminal patients to maximally maintain physical, emotional, spiritual and social abilities caused by their illness as well as actions in an effort to achieve recovery, where the quality of life includes holistic aspects, namely physical health, psychological status, level of freedom, environment and social relations. The purpose of this study was to analyze the correlation between palliative care management and the quality of life of terminal patients in the ICU of RSUD dr. Haryoto Lumajang Methods: The research design used in this study is correlational analysis. The population of this study was terminal patients who were treated in the ICU at RSUD dr. Haryoto Lumajang with a monthly average. The sample in this study was terminal patients who were treated in the ICU of RSUD dr. Haryoto Lumajang taken by purposive sampling technique that reached 33 people. Data were collected using the FACIT-Pal questionnaire & IPOS questionnaire, and analysed using the Spearman Rank test. Results: The results of the study showed that the management of palliative care in the ICU of RSUD dr. Haryoto Lumajang showed quite good results (60.6%), and the quality of life of terminal patients in the ICU room of RSUD dr. Haryoto Lumajang showed quite good results (57.6%). The results of the analysis test using the SPSS with the Spearman Rank test obtained p = 0.004 with a significance level of 0.05 (p value = 0.004 ≤ 0.05), which means that there is a correlation between management of palliative care and quality of life of terminal patients in the ICU of RSUD dr. Haryoto Lumajang Conclusion: Based on the results of research showing that there was a correlation between palliative care management and the quality of life of terminal patients, nurses must improve palliative care services to achieve holistic well-being which includes physical, psychological, social and spiritual for terminal patients. The better palliative care provided the better the the quality of life of terminal patients